Vancomycin Utilization Evaluation: Are We Dosing Appropriately? - Ladan Ayazkhoo; Sarah Mousavi; Farnaz Ramazani; Maryam Ayatollahi-Tafti; Zeinab Sa'dabadi; Mohammad Sistanizad (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Inappropriate use of vancomycin not only increase health care costs but also contribute to the emergence of resistant organisms. Higher trough serum vancomycin concentrations (>10mg/L) has been recommended for avoidance of development of resistance. We aim to compare the administered dose with recommended doses based on guideline-recommended weight-based dosing. Methods: In a cross sectional study, all patients who received vancomycin between July and October 2013, in infectious disease, internal medicine wards and emergency department of a teaching hospital in Tehran, Iran were entered to the study. Indication of vancomycin and necessary data for dose calculation including height and serum creatinine were recorded. Prescribed doses were compared with recommended doses in guidelines and calculated Glomerular filtration rate (GFR) for each patient. Results: One hundred and four patients (45 females and 59 males) recruited in the study. Our results indicated that, from all administered doses of vancomycin, 64.4% and 88.8% differs significantly (more than 20%) based on American Pharmacist Association (AphA) vancomycin monograph and guideline-recommended, weight-based vancomycin dosing (for adults), respectively. Conclusion: Underdosing of vancomycin is a major risk factor for developing resistance of gram positive organisms to this glycopeptide. Our results showed that more than half of patients receiving vancomycin are in the risk of low drug levels based on guidelines. So, having a comprehensive plan for the proper use of this drug especially designing effective internal guidelines can prevent emergence of resistance to vancomycin in future.